(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Corruption in the process of obtaining social assistance can have profound implications on family relationships. This scientific article delves into the multifaceted ways in which corruption within social welfare systems can strain familial bonds, exacerbate socio-economic disparities, and impede the well-being of individuals and families. By exploring case studies, research findings, and theoretical frameworks, this article sheds light on the detrimental effects of corruption in accessing social support on family dynamics. Strategies for combating corruption and promoting transparency in social assistance programs are also discussed to mitigate its adverse consequences on family relationships.